2003
DOI: 10.1046/j.1365-2958.2003.03581.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the heat shock response is independent of DnaK and σ32 levels in Caulobacter crescentus

Abstract: Summary Expression of heat shock genes in Gram

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 47 publications
4
40
0
Order By: Relevance
“…The rpoH genes from Caulobacter crescentus (51), Rhodobacter capsulatus (10), and Agrobacterium tumefaciens (33) are positively autoregulated from an RpoH-dependent promoter upon heat shock. In C. crescentus, down-regulation of the stress response is independent of DnaK and RpoH (9). In A. tumefaciens, DnaK-dependent regulation of RpoH has also been shown to occur at the level of activity (34).…”
mentioning
confidence: 99%
“…The rpoH genes from Caulobacter crescentus (51), Rhodobacter capsulatus (10), and Agrobacterium tumefaciens (33) are positively autoregulated from an RpoH-dependent promoter upon heat shock. In C. crescentus, down-regulation of the stress response is independent of DnaK and RpoH (9). In A. tumefaciens, DnaK-dependent regulation of RpoH has also been shown to occur at the level of activity (34).…”
mentioning
confidence: 99%
“…The overexpressing strain NA1000 pRB51 carries a multicopy plasmid in which the groESL genes are under the control of the P xylX promoter (7). Thus, in the presence of xylose the levels of GroES/GroEL are two to threefold higher than in those in the control strain NA1000 pAS22, which carries only the chromosomal copy of the groESL genes (7). As the results shown in Table 3 indicate, ␤-galactosidase activity in C. crescentus cells carrying transcription fusion pMA11 was 30% lower in cells overexpressing GroES/GroEL (NA1000 pRB51) than in cells presenting normal levels of these chaperones (NA1000 pAS22).…”
Section: Resultsmentioning
confidence: 92%
“…Given that dnaK is essential in C. crescentus (19,20), we pursued a strategy to generate a minimal functional allele of dnaK. Based on the high-density Tn sequencing data of Christen et al (20), we noted that C. crescentus tolerates Tn5 insertions at the 3= end of dnaK, after codon 496.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to E. coli, DnaK is essential for growth in C. crescentus (19). However, removing the alpha-helical lid domain at the C terminus of DnaK does not have a significant effect on C. crescentus growth; three independent genetic studies have identified viable strains bearing transposon insertions (20), frameshift mutations (34), or nonsense mutations (this work) in the linker that connect the lid domain to the substrate binding beta sheet domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation